A Common Threat Analysis of Intergovernmental Policy Convergence in the Framework of Regional Integration: A Case Study of the ASEAN Strategic Partnership â€œOur Eyesâ€ - Usuluddin, Fachruddin; Widodo, Pujo; Amiruddin, Barik Ali (Jurnal Hubungan Internasional, 2019)
Since 2016, there has been a significant increase in the incidence of terrorist attacks in several ASEAN Member States (AMS). In response, Indonesia initiated the formation of an intelligence information exchange cooperation namely Our Eyes Initiative (OEI) to several AMS and communicated that the transnational terrorist network is a common threat. Some are optimistic, this cooperation will result an effective regional integration, while others are sceptical that the condition of the region is still tinged with economic, defence competition and super power states dominance such as China and America so that it affects the cooperation. This study aims to analyze how transnational terrorism encourages AMS to use the transnational communication mechanism from Holzinger and Knill in the OEI cooperation. This research is a part of International Relations studies so that researchers make the traditional realist/neorealist paradigm as a basis in explaining regional conditions. The study use qualitative explanative method. Data collection were obtained through secondary sources and analyzed by means of data comparison, verification and conclusion drawing. So far, the cross-national convergence study has come to the finding that convergence among countries is present due to the influence of regional institution so as to create policy product adopted by each state. However, the authors argue that in the OEI case study is primarily influenced by a common threat so that the state responds and creates a transnational communication mechanism.